Shiloh : a biblical city in tradition and history - Schley, Donald G. (JSOT Press, 1989)
This work is the first comprehensive treatment of the biblical traditions pertaining to the Israelite sanctuary at Shiloh. A survey of previous research puts the current discussion of Shiloh into historical context and exposes the real issues behind the often bitter debate over Shiloh's supposed destruction during the Philistine wars and its traditional status as the first 'central' shrine.
Keywords: Bible. -- Former Prophets -- Criticism, interpretation, etc.; Bible. -- Prophètes antérieurs -- Critique, interprétation, etc.; Bible. -- Former Prophets; Bible. -- A.T. -- Critique, interprétation, etc.; Documentary hypothesis (Pentateuchal criticism); Shiloh (Extinct city) -- History.; West Bank -- Antiquities.; Shiloh (Extinct city); Shiloh (Extinct city) -- Biblical teaching.; Silo (Ville ancienne); Silo (Ville ancienne) -- Enseignement biblique.; Théorie documentaire (Critique du Pentateuque); Silo (Ville ancienne) -- Histoire.; Cisjordanie -- Antiquités.; RELIGION -- Judaism -- Sacred Writings.; RELIGION -- Biblical Studies -- Old Testament.; Biblical teaching; Antiquities; West Bank; West Bank -- Shiloh (Extinct city); Silo (ville ancienne); Palestine, ancient period. -- Historical sources: Bible -- O.T; Criticism, interpretation, etc.; History